1990
DOI: 10.1111/j.1346-8138.1990.tb03714.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 1,24R‐dihydroxyvitamin D3 on the Growth of Human Keratinocytes

Abstract: The effect of 1,24R-dihydroxyvitamin D3 (1,24R(OH)2D3), a synthetic analogue of a biologically active form of vitamin D3 (1,25-dihydroxyvitamin D3, 1,25(OH)2D3), on the growth of human keratinocytes cultured in serum-free medium was investigated. The growth of cultured normal human keratinocytes was inhibited by 65% by 10(-8)M 1,24R(OH)2D3 and by 90% by 10(-7)M 1,24(OH)2D3. It inhibited cell growth almost completely at 10(-6)M. The DNA synthesis of keratinocytes was also inhibited with 1,24R(OH)2D3 by 27% at 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
1

Year Published

1992
1992
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(42 citation statements)
references
References 20 publications
(19 reference statements)
2
39
1
Order By: Relevance
“…This is in contrast with studies which showed that tacalcitol affects keratinization to some extent [2,7,24]. However, most authors conclude that the effect of tacalcitol on differentiation is limited [4,6,8].…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…This is in contrast with studies which showed that tacalcitol affects keratinization to some extent [2,7,24]. However, most authors conclude that the effect of tacalcitol on differentiation is limited [4,6,8].…”
Section: Discussioncontrasting
confidence: 53%
“…Several in vitro and in vivo studies showed the effect of tacalcitol on epidermal proliferation and differentiation, and the effect on inflammatory processes in skin [2][3][4][5][6][7][8]. Especially the effect on epidermal proliferation has shown to be most substantial [2,6,7]. This finding strongly suggests that the antipsoriatic effect of tacalcitol may be mediated by the normalization of epidermal cell cycle kinetics.…”
Section: Introductionmentioning
confidence: 58%
“…For maxacalcitol, the affinity is slightly weaker than that of calcitriol (Valaja et al 1990) and is almost the same as that of calcipotriol (Binderup & Bramm 1988). The affinity of tacalcitol is comparable with that of calcitriol (Matsumoto et al 1990). Alfacalcidol does not directly bind to the WT-VDR in vitro because it is a prodrug converted to calcitriol via hydroxylation in the liver (Orimo & Schacht 2005).…”
Section: Discussionmentioning
confidence: 68%
“…Synthetic VD 3 analogs are important therapeutic agents for treating renal osteodystrophy, psoriasis vulgaris, osteoporosis, and other diseases (Matsumoto et al 1990, Brown & Coyne 2002, Morii et al 2004, Tsukamoto 2004, O'Neill & Feldman 2010. Among the VD 3 analogs, calcitriol is the physiologically active form of VD 3 , and alfacalcidol is a prodrug that requires hydroxylation in the liver.…”
Section: Introductionmentioning
confidence: 99%
“…Tacalcitol, a chemically synthesized vitamin D 3 analog, has been demonstrated to produce equivalent dose-dependent inhibition of proliferation and stimulation in the terminal differentiation of human keratinocytes [5, 6, 7]. Tacalcitol is as active as calcitriol (1α,25-dihydroxyvitamin D 3 ) on mineral metabolism, but is less toxic than 1α-hydroxyvitamin D 3 [8].…”
Section: Discussionmentioning
confidence: 99%